Pengaruh Kinerja Keuangan Dan Risiko Sistematis Terhadap Return Saham Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2019 - Dinda Intania Karina Cindi Nurhardana; Agus Widarko; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2021)
Abstract The purpose of this study is to describe the financial performance consisting of net profit margin, return on equity and earning per share, and systematic risk and to know the influence and analyze financial performance consisting of net profit margin, return on equity and earning per share, and systematic risk to stock returns simultaneously and partially. This type of research uses a quantitative approach. The sample of this research is a mining company listed on the Indonesia Stock Exchange for the period 2017-2019 using purposive sampling method, namely as many as 3 companies. Data collection method by collecting and analyzing company financial data available on the Indonesia Stock Exchange. The analytical method used in this study was multiple linear analysis with SPSS 25.0 for windows. The results showed that: 1) There is a positive and significant influence of net profit margin, return on equity and earning per share, and systemic risk simultaneously to the rerun of mining companies. 2) There is a negative influence of net profit margin on the return of shares on mining companies. 3) There is a negative effect of return on equity on the return of mining companies. 4) There is a positive and significant influence of earning per share on the return of shares of mining companies. 5) There is a positive and significant effect of systematic risk to the return of shares of mining companies. Keywords: Financial Performance, Net Profit Margin, Return On Equity, Earning Per Share, and Systematic Risk.